In-depth Knowledge of the Role of the Clinical Mentor - Soto Núñez, Claudia; Reinoso, Lissette Avilés; Lucchini Raies, Camila; Fuentes, Paz Soto (Investigación y Educación en Enfermería, 2017)
Objective. This work sought to unveil the meaning expressed by clinical nurses by being mentors for students from the nursing internship level. Methods. Phenomenological research. In-depth interviews were conducted with nine clinical nurses from a hospital in Santiago de Chile, who participate as mentors of nursing students in their last stage of university formation. Results. Four comprehensive categories were obtained with their respective units of meaning by nursing: 1) vocation and gratification, 2) personal and professional challenge, 3) big responsibility, and 4) transmission of experience. Conclusion. Clinical mentorship is a relevant experience in the professional lives of nurses, which implies overcoming challenges, self-training, and delivering the best of oneself, for the purpose of training future professionals prepared to practice nursing integrally. How to cite this article: Soto C, Avilés L, Lucchini C, Soto P. In-depth Knowledge of the Role of the Clinical Mentor. Invest. Educ. Enferm. 2017; 35(3): 356-363.